Quality of Public Services Through Online Single Submission (OSS) at the Blora Investment and One-Stop Integrated Service Office - Listiana Puspitasari, Heni; Suprastiyo, Ahmad; Junadi, Junadi (Universitas Muhammadiyah Gorontalo, 2024)
The quality of public services is an important factor in building public trust and satisfaction. In Indonesia, the Online Single Submission (OSS) system was introduced to simplify the licensing process and increase transparency. In Blora, DPMPTSP manages OSS implementation, but challenges such as service instability, slow response, and technical issues are still found. This research aims to analyze the influence of public administration services through the Online Single Submission (OSS) system at the Blora Investment and One Stop Integrated Services Service (DPMPTSP) This study uses a qualitative descriptive approach to understand the influence of the service quality of the Online Single Submission (OSS) system on user satisfaction at DPMPTSP Blora. The data was collected through semi-structured interviews and observations, focusing on timeliness, officer response, and user barriers. The sample was purposively selected from employees involved in OSS management, with data validation through source triangulation and expert consultation. The results of the research in show that the inline single submission (OSS) system at the Blora Investment and One-Stop Integrated Services (DPMPTSP) has a positive impact on the efficiency of licensing service. The OSS system at DPMPTSP Blora improves licensing efficiency, supports the economy, and is supported by infrastructure and human resource development. Challenges such as limited human resources, internet access, and information need to be overcome to make OSS an inclusive and sustainable public service model.